Pelatihan Speaking English untuk Siswa SMK Negeri 1 Dolo Barat - Mawardin M Said; Hasna; Budi; Aminah Suriaman; Ibmasiah Wardatun Islamiyah Mawardin; Ide Ilmiah Mawardin; Istianah Mawardin; Ilmuislami Mawardin; Siti Aisyah Al Munawwaroh (Universitas Negeri Surabaya, 2025)
This Community Service aims at training students of SMKN (Sekolah Menengah Kejuruan Negeri, Government Vocational High School) 1 West Dolo for speaking English. They hopefully can apply it for speaking English to others so that they can communicate in the foreign language orally. They were motivated to master English to communicate in the international language practically. Its specific traget was the students who have spirits in learning to speak English. They then can communicate in the global language so that they become global learners. Communicative method is used to reach the objecive. Its result hopefully that through this Training the students can speak English by using simple sentences. This Article may be a reference for anyone who needs it.